2015
DOI: 10.1002/smll.201500892
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Drug Delivery Nanoparticles from Human Plasma Using an Electrokinetic Platform Technology

Abstract: The effect of complex biological fluids on the surface and structure of nanoparticles is a rapidly expanding field of study. One of the challenges holding back this research is the difficulty of recovering therapeutic nanoparticles from biological samples due to their small size, low density, and stealth surface coatings. Here we present the first demonstration of the recovery and analysis of drug delivery nanoparticles from undiluted human plasma samples through the use of a new electrokinetic platform techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…None of these solutions are ideal. This said, examples of commercial planar electrode arrays (Biological Dynamics, San Diego, CA), are seen in , which shows that this architecture has found success with high conductance solutions, and provides an empirical reference for further designs. Nevertheless, even these devices, designed to operate with high conductance solutions, have performance limitations due to adverse electrochemical effects when driven above recommended voltages or below recommended frequency of operation.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…None of these solutions are ideal. This said, examples of commercial planar electrode arrays (Biological Dynamics, San Diego, CA), are seen in , which shows that this architecture has found success with high conductance solutions, and provides an empirical reference for further designs. Nevertheless, even these devices, designed to operate with high conductance solutions, have performance limitations due to adverse electrochemical effects when driven above recommended voltages or below recommended frequency of operation.…”
Section: Introductionmentioning
confidence: 93%
“…Electrokinetic separation devices offer tremendous promise in terms of miniaturization and direct separation of targeted biomarkers without the need to go through centrifugation, chemical isolation, and precipitation steps. New devices, which can operate under high conductance conditions (>0.5 S/m), have now been used to isolate cancer related cf‐DNA and drug delivery nanoparticles from un‐diluted blood and plasma samples. There is also research into using DEP to concentrate relevant biomarkers for chemical assay .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Heller group developed a dielectrophoretic method for the recovery of drug delivery nanoparticles as well as cancer related biomarkers from plasma and blood. 66,67 This approach can be used for the isolation and detection of EVs as well.…”
Section: Affinity-based Isolationmentioning
confidence: 99%
“…He derived volumetric flow rate and pressure distribution and concluded that the wall shear stress and pressure drops are at a maximum at the throat of each stenosis and a minimum at the ends of each stenosis. Another important development in the history of bio-fluids is the investigation of nanoparticle separation technology which can be used to isolate a wide range of nanoparticles out of plasma with a minimum amount of manipulation [17]. This latest discovery enables researchers to study the mathematical modeling of drug delivery nanoparticle systems in blood flow.…”
Section: Introductionmentioning
confidence: 99%